Antibacterial activity test of (+)- katekin and gambir (uncaria gambier roxb.) against some types of grambled bacteries negative bacteria and their mechanism - Syifa Monica; Zikri Husna (Institute of Accounting Research and Novation (IARN), 2022)
There is evidence that catechins and aqueous extracts of the gambir plant (Uncaria gambier Roxb.) has antibacterial action. The purpose of this research was to further evaluate the antibacterial activity of (+)- catechins and an aqueous extract of gambir against Shigella flexneri, Pseudomonas aeruginosa, Escherichia coli, Proteus vulgaris, and Proteus mirabilis. As part of the procedures that were carried out, sensitivity testing to gram-negative bacteria was performed to validate the activity. antimicrobial (+)- catechins and gambier water extract, calculation of the Minimum Inhibitory Concentration (MIC), and analysis of the mechanism of inhibition against gram-negative bacteria were all part of this study. The findings of this research show that the minimum inhibitory concentration (MIC) level for (+)- catechins against Shigella flexneri bacteria is 7.5 mg/ml. The mechanism of action of (+)- catechins is to disrupt cell membranes, which then leads to the leakage of cell components. Ca2+ ions and K+ ions, together with proteins and nucleic acids, were found to be present in the bacterial cell medium, which provided evidence that this was the case. In the meantime, the macrodilution technique revealed that the gambier water extract did not exhibit any inhibitory effect at any concentration up to 25 mg/ml